ANALISIS PEMAHAMAN KONSEP SISWA PADA MATERI PERKEMBANGBIAKAN TUMBUHAN MENGGUNAKAN INSTRUMEN TES DIAGNOSTIK TWO TIER - Safira, Utin Trisna; Wahyu Kurniawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This quantitative descriptive study aims to analyze the performance of grade IV A and IV B students in understanding the concept of plant reproduction. The results showed that around 68% students are not sure about their own concepts a very high percentage of misunderstandings. These misunderstandings mainly occurred in the concepts of plant body parts, photosynthesis, and plant reproduction. The main causes of misunderstandings are circumstances, teacher teaching strategies, and students themselves. This study suggests that future researchers can improve misunderstandings about plant reproduction material in science learning, so that they can improve students' understanding and performance in understanding the concept of plant reproduction.